An electrophysiological megastudy of spoken word recognition. Issue 8 (14th September 2018) - Winsler, Kurt; Midgley, Katherine J.; Grainger, Jonathan; Holcomb, Phillip J.
ABSTRACT: This study used electrophysiological recordings to a large sample of spoken words to track the time-course of word frequency, phonological neighbourhood density, concreteness and stimulus duration effects in two experiments. Fifty subjects were presented more than a thousand spoken words during either a go/no go lexical decision task (Experiment 1) or a go/no go semantic categorisation task (Experiment 2) while EEG was collected. Linear mixed effects modelling was used to analyze the data. Effects of word frequency were found on the N400 and also as early as 100 ms in Experiment 1 but not Experiment 2. Phonological neighbourhood density produced an early effect around 250 ms and the typical N400 effect. Concreteness elicited effects in later epochs on the N400. Stimulus duration affected all epochs and its influence reflected changes in the timing of the ERP components. Overall the results support cascaded interactive models of spoken word recognition.